Correlation Between Automatic Short Answer Scoring and Manual Scoring by Teacher on Indonesian Assessments - Ayu, Ravika; Nurjanah, Dade (JTP - Jurnal Teknologi Pendidikan, 2025)
Assessment is one tool evaluation in the learning teaching process to determine quality of learning. One of method being assessed Enough complicated in the assessment process is essay test. The essay test requires more time lots in the proofreading process as well as low validity and reliability because possible essay assessment influenced element subjective. Therefore, needed application used for correct essay answers expected automatically can help teachers to correct answer with fast and more results objective namely Automated Short Answer Scoring (ASAS). This research use sentence embedding method for measure similarity meaning between answer key and students answer. Data sets used consists of two data. One data consists of 1200 pairs of answer keys and students answer used for train the model. Two data totaling 250 words is used for evaluate models. Before enter the sentence embedding process, answering will through the pre-processing stage is remove stop words, remove empty, case folding, delete number, delete punctuation. Testing this system will done with method compare assessment carried out system with assessment carried out by teachers conventional use coefficient correlation. The result of test coefficient correlation Pearson of 0.81 and concluded reached 81 % similar with human rater assessment. This study can help teachers to be more efficient in the assessment.